Working time reforms in times of crisis - Lang, Carole; Clauwaert, Stefan; Schömann, Isabelle (Brussels, 2013)
" This working paper extends and complements the analysis of pre-2012 anticrisis measures published in the earlier ETUI Working Paper 'The crisis and'national labour law reforms: a mapping exercise' which dealt with anti-crisis measures on working time taken before February 2012.